Excess Opioid Disposal Following Orthopaedic Surgery: A Randomized Clinical Trial. Issue 6 (December 2022) - Keyser, Cornelia; Bhashyam, Abhiram; Abdurrob, Abdurrahman; Smith, Jeremy T.; Bluman, Eric; Chiodo, Christopher
Background: Previous research indicates low disposal rates of excess postoperative narcotics, leaving them available for diversion or abuse. This study examined the effect of introducing a portable disposal device on excess opiate opioid disposal rates after lower extremity orthopaedic surgery. Methods: This was a single site randomized control trial within an outpatient orthopaedic clinic. All patients 18 years or older, undergoing outpatient foot and ankle surgery between December 1, 2017 and August 1, 2018 were eligible. Patients were prospectively enrolled and randomized to receive standard opioid disposal instructions or a drug deactivation device at 2-week postoperative appointments. Participants completed an anonymous survey at 6-week postoperative appointments. Results: Of the 75 patients surveyed, 68% (n = 26) of the experimental group and 56% (n = 21) of the control group had unused opioid medication. Of these, 84.6% of patients who were given Deterra Drug Deactivation System deactivation pouches safely disposed of excess medication, compared with 38% of controls (P = .003). When asked if they would use a disposal device for excess medication in the future, 97.4% (n = 37) of the experimental and 83.8% (n = 31) of the control group reported that they would. Conclusions: Providing a portable disposal device with postoperative narcotic prescriptions may increase safe disposal rates of excess opioid medication following lower extremity orthopaedic surgery. Levels of Evidence: Level I